RESPON DOSEN PTAI YOGYAKARTA TERHADAP KONSEP USHULFIQH JASSER AUDA - Muharram, Tamyiz (JURNAL TAPIS, 2015)
ABSTRACTÂ Reconstruction maqashid al-Shariah concept initiated by Jasser Auda provides fresh air in the middle of stagnation usul al-fiqh paradigm. However, thinking about maqashid Jasser Auda al-shariah with systems theory approach gets critical response from the lecturers PTAI in Yogyakarta, where the tradition of usul al-fiqh long since has appeared in the region. This research is a qualitative descriptive with reference to the type of field research. The subjects of this study is a lecturer PTAI in Yogyakarta predetermined purposively. To find out how the response PTAI lecturer in Yogyakarta to the idea of reconstruction maqashid al-Shariah offered Jasser Auda, this study utilized the theory of reader-response criticism. From the results, the response, such as: First, the methodological framework, philosophical, and theoretical Jasser Auda is not based on the discourse that is more fundamental, so thought Jasser Auda seemed deprived of the most fundamental roots in the context of Islamic scholarship. Secondly, the idea maqashid al-Sharia Jasser Auda is not applicable version, so it can not answer the practical question of Muslims. Yet since the beginning Jasser Auda would like to entail various extremities and try to sit in a neutral position. Third, new ideas and Jasser Auda is still stuck in the legal framework, and ignoring the cultural framework that is much more universal and fundamental. So that any legal product that is produced using the frame maqashid al-Shariah version Jasser Auda impressed not only a functional law, even uprooted from their social roots.Â Key words: Jasser Auda, Maqashid al-Syariah, reader-response criticism.Â